ANALISIS POLA SEBARAN KARAKTERISTIK IKLIM DI PULAU SUMBAWA - YASA, I WAYAN; SALEHUDIN, SALEHUDIN; SAIDAH, HUMAIRO; JAYANEGARA, I DEWA GEDE; SULISTIYONO, HERI (Universitas Mahasaraswati K. Mataram, 2023)
Sumbawa Island is one of the largest islands in West Nusa Tenggara (NTB) Province with an area of 15,414.5 km². Climatic conditions greatly influence the economy of the people of Sumbawa Island because most of the population earns their living as farmers, planters and livestock breeders. Extreme climate changes often occur. This results in natural disasters such as floods, landslides and drought. Sumbawa Island itself often experiences floods in the rainy season and droughts in the dry season. Knowledge of climate characteristics will really help the people there, in overcoming and avoiding the impacts of extreme climate change now and in the future. This research functions to provide information regarding the climate characteristics of Sumbawa Island.The method used to analyze the climate characteristics of Sumbawa Island is the Thornthwaite and Schmidth-Fergusson climate classification methods. The data used is secondary data for 14 years (2005-2018). This data was obtained from the NT I River Basin Center and generation data using the Thomas-Fiering model for the next 10 years (2019-2028).The results of the analysis showed that according to Thornthwaite, Sumbawa Island in the 2005-2018 and 2019-2028 periods had the same climate type, namely a dry climate (E) based on an average PE index value < 16 and a tropical climate (A) based on an average TE index value. ≥ 128. According to Schmidth-Fergusson in the 2005-2018 and 2019-2028 periods, Sumbawa Island has the same 3 types of climate, namely a moderate climate (D) with a value of 0.6 ≤ Q < 1, a slightly dry climate (E) with a value of 1 ≤ Q < 1.67 and dry climate (F) with a value of 1.67 ≤ Q < 3.